Columnar silicon anode with carbon fiber network and lithium ion battery comprising same

By forming a random multi-directional carbon fiber network on the columnar silicon anode of the lithium-ion battery pack, the stress and strain problems caused by volume changes during the cycle of the silicon anode are solved, and the rate performance is improved, achieving a higher battery pack performance.

CN119495699APending Publication Date: 2025-02-21GM GLOBAL TECHNOLOGY OPERATIONS LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311050357.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The huge volume changes caused by lithiation and deliquification in the lithium-ion battery pack in the silicon anode during circulation lead to stress and strain, resulting in electrode fracture and electrical isolation from the current collector, and the low inherent conductivity of the silicon anode limits the rate performance.

Method used

The columnar silicon anode consisting of multiple spherical silicon columns and a random multi-directional carbon fiber network on the exposed surface of the spherical silicon column. The carbon fiber network consists of carbon nanotubes and polymer dispersant to deposit the silicon column by plasma vapor deposition. And form a carbon fiber network at an elevated temperature.

Benefits of technology

It reduces the expansion and contraction problems of silicon anode during circulation, improves capacity and minimizes faults of the battery pack, and enhances rate performance, especially in high-power applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495699A_ABST
    Figure CN119495699A_ABST
Patent Text Reader

Abstract

A lithium ion battery comprising a columnar silicon anode comprising a carbon fiber network on an exposed surface of the columnar silicon anode is provided. The columnar silicon is formed by a plasma vapor deposition method. Also disclosed are methods for forming a carbon fiber network that generally include spraying a dilute carbon fiber precursor solution comprising carbon nanotubes, optionally a polymeric dispersant, and a solvent, and then mildly evaporating it at an elevated temperature to remove the solvent and form a carbon fiber network. The carbon fiber network is uniformly and multidirectionally disposed on the exposed surface of the columnar silicon anode. The presence of the carbon fiber network provides a high electron path to enhance the battery pack power capacity, especially at higher current rates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates generally to anodes for liquid-based, gel-based or solid-state lithium-ion batteries, and more particularly to anodes formed of columnar silicon having a carbon fiber network thereon and lithium-ion batteries including the same. Background Art

[0002] Lithium-ion batteries including silicon (Si) anodes are a promising energy storage technology due to their high energy density compared to conventionally used graphite anodes (372 mAh g -1 ) compared to its weight theoretical lithium (Li) storage capacity (for Li 4.4 Si is 4200mAh g -1 ), while also having a relatively low discharge voltage (the average delithiation voltage of Si is 0.4V).

[0003] However, silicon's ability to accommodate large amounts of lithium is known to cause the material to undergo large volume changes during lithiation and delithiation that occur during battery cycling, which can be as high as about 400% or more. During repeated cycling, the stress and strain caused by this volume change can cause the electrode to fracture and electrically isolate from the underlying current collector, resulting in delamination of the deposited silicon film from the current collector. In addition, silicon anodes suffer from mechanical fracture and instability of the solid-electrolyte-interface (SEI) layer formed during the intercalation / deintercalation process.

[0004] Furthermore, silicon anodes are inherently subject to low intrinsic conductivity (<10 -5 Siemens / cm (S / cm)), which is significantly lower than the intrinsic conductivity of carbon and graphite (10-10 4 S / cm). When working with liquid electrolytes (or solid electrolytes or gel electrolytes), the low conductivity of silicon can degrade the rate performance of lithium-ion batteries, hindering their practical high-power applications.

[0005] Therefore, it is desirable to mitigate the problems caused by the expansion and contraction of silicon anodes during cycling of lithium-ion batteries to maximize capacity and minimize failures as well as to improve their rate capabilities for high power applications. Summary of the invention

[0006] In an exemplary embodiment, a columnar silicon anode for a lithium ion battery includes a plurality of spherical silicon pillars; and a carbon fiber network on an exposed surface of the spherical silicon pillars. The silicon in the plurality of spherical silicon pillars is greater than 97 weight percent, and the carbon fiber network is about 0.05 weight percent to less than 3 weight percent, wherein the weight percentage is based on the total weight of the plurality of spherical silicon pillars and the carbon fiber network.

[0007] The carbon fiber network is random and multi-directional. In one or more aspects, the carbon fiber network also includes a polymer additive greater than 0 to 3 weight %. The carbon fiber network includes carbon nanotubes, wherein the carbon nanotubes have a length greater than about 1 micron (μm), a diameter of about 1nm to about 6nm, and a thickness less than 0.1 nanometer (nm). The carbon nanotubes may include single-walled carbon nanotubes, double-walled carbon nanotubes, and / or multi-walled nanotubes. In some aspects, the carbon fiber network includes one or more carbon additive materials.

[0008] A plurality of spherical silicon pillars can be deposited onto an anode current collector by DC magnetron sputtering. Each of the plurality of spherical silicon pillars includes a and b dimensions with a length ranging from about 0.5 to about 40 micrometers (μm). The columnar silicon anode has an area capacity of about 0.5 to about 20 milliampere hours per square centimeter. A lithium-ion battery pack including a columnar silicon anode can be used with a liquid-based, solid-based, or gel-based electrolyte.

[0009] In one or more embodiments, a method for forming a carbon fiber network on a columnar silicon anode of a lithium ion battery includes providing a columnar silicon anode on an anode current collector, wherein the columnar silicon anode includes a plurality of spherical silicon columns deposited on the anode current collector by plasma vapor deposition. A carbon fiber precursor solution having a solid content of less than 10% by weight is deposited on the exposed surface of the columnar silicon anode. The carbon fiber precursor solution comprises carbon nanotubes, a polymer dispersant, and a solvent. The deposited carbon fiber precursor solution, the columnar silicon anode, and the anode current collector are subjected to an elevated temperature for a period of time to effectively evaporate the solvent and form a carbon fiber network on the exposed surface, wherein the carbon fiber network is random and multi-directional, and the carbon fiber network is greater than 0 to less than 3% by weight based on the total weight of the carbon fiber network and the columnar silicon anode. The columnar silicon anode comprises greater than 97% by weight of silicon based on the total weight of the carbon fiber network and the columnar silicon anode.

[0010] The elevated temperature may be 80°C to 90°C and the solvent may include water or N-methyl-2-pyrrolidone.

[0011] The anode current collector has a surface roughness Rz of 0.1 μm to 12 μm.

[0012] The polymer dispersant includes poly(vinylidene fluoride) (PVDF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), poly(tetrafluoroethylene) (PTFE), sodium carboxymethylcellulose (CMC), styrene-butadiene rubber (SBR), nitrile rubber (NBR) or styrene ethylene butylene styrene copolymer (SEBS). The carbon nanotube has a diameter of about 1 to about 6 nanometers (nm), a thickness of less than 0.1 nm and a length of greater than 1 μm. The carbon fiber precursor solution may further include a carbon material including acetylene black, graphene and / or graphite.

[0013] In one or more embodiments, a rechargeable lithium ion battery includes a cathode current collector having a thickness of about 4 to about 30 μm externally connected to a load, the cathode current collector comprising aluminum; a cathode on the cathode current collector; an anode current collector having a thickness of about 4 to about 30 μm externally connected to a load, wherein the anode current collector is made of one or more materials selected from the group consisting of copper, stainless steel, nickel, iron, titanium, tin (Sn) and alloys thereof, and wherein the anode current collector has a surface roughness R of 0.1 μm to 12 μm. z ; A columnar silicon anode on the anode current collector, the columnar silicon anode comprising a plurality of spherical silicon columns and a carbon fiber network on the exposed surfaces of the spherical silicon columns.

[0014] The columnar silicon anode is deposited by plasma vapor deposition and has a thickness of 1 μm to about 80 μm, wherein the columnar silicon anode contains more than 97 wt % silicon, and wherein the columnar silicon anode has a capacity of about 0.5 to about 20 mAh / cm 2 area capacity.

[0015] A porous separator is between the cathode and the columnar silicon anode.

[0016] In one or more aspects, the lithium-ion battery may further include a liquid electrolyte in the cathode, the columnar silicon anode, and the porous separator, wherein the liquid electrolyte comprises a lithium salt and an organic solvent, wherein the liquid electrolyte comprises a lithium salt, an organic solvent, and optional additives, wherein the lithium salt comprises LiPF6, LiBF4, lithium bis(oxalate)borate, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiAsF6, LiC(CF3SO2)3, LiClO4, Li 1+x Al x Ti 2-x (PO4)3 and LiTFSI, and wherein the organic solvent comprises ethylene carbonate, diethyl carbonate, propylene carbonate, fluoroethylene carbonate (FEC) and combinations thereof.

[0017] The separator is a solid electrolyte, and in the cathode and the columnar silicon anode, wherein the solid electrolyte is selected from pseudo binary sulfide, pseudo ternary sulfide, pseudo quaternary sulfide, halide-based solid electrolyte and hydride-based solid electrolyte.

[0018] The present invention discloses the following technical solutions.

[0019] Scheme 1. A columnar silicon anode for a lithium-ion battery, comprising:

[0020] a plurality of spherical silicon pillars; and

[0021] A carbon fiber network on the exposed surface of the spherical silicon pillar,

[0022] wherein the silicon in the plurality of spherical silicon pillars is greater than 97 weight percent, and wherein the carbon fiber network is about 0.05 weight percent to less than 3 weight percent, wherein the weight percentages are based on the total weight of the plurality of spherical silicon pillars and the carbon fiber network.

[0023] Option 2. A columnar silicon anode according to Option 1, wherein the carbon fiber network is random and multi-directional.

[0024] Option 3. A columnar silicon anode according to Option 1, wherein the carbon fiber network further comprises greater than 0 to 3 weight percent of a polymer additive.

[0025] Option 4. A columnar silicon anode according to Option 1, wherein each of the plurality of spherical silicon pillars comprises a and b dimensions with a length ranging from about 0.5 to about 40 micrometers (μm).

[0026] Option 5. A columnar silicon anode according to Option 1, wherein a lithium-ion battery pack including the columnar silicon anode includes a liquid-based, solid-state or gel-based electrolyte.

[0027] Option 6. A columnar silicon anode according to Option 1, wherein the carbon fiber network comprises carbon nanotubes, wherein the carbon nanotubes have a length greater than about 1 micrometer (μm), a diameter of about 1 nm to about 6 nm, and a thickness less than 0.1 nanometers (nm).

[0028] Option 7. A columnar silicon anode according to Option 6, wherein the carbon nanotubes include single-walled carbon nanotubes, double-walled carbon nanotubes and / or multi-walled nanotubes.

[0029] Option 8. A columnar silicon anode according to Option 6, wherein the carbon fiber network further comprises one or more carbon additive materials.

[0030] Option 9. A columnar silicon anode according to Option 1, wherein the plurality of spherical silicon pillars are deposited onto the anode current collector by DC magnetron sputtering.

[0031] Option 10. A columnar silicon anode according to Option 1, wherein the columnar silicon anode has an area capacity of about 0.5 to about 20 milliampere hours per square centimeter.

[0032] Scheme 11. A method for forming a carbon fiber network on a columnar silicon anode of a lithium-ion battery, the method comprising:

[0033] providing a columnar silicon anode on an anode current collector, wherein the columnar silicon anode comprises a plurality of spherical silicon pillars deposited onto the anode current collector by plasma vapor deposition;

[0034] depositing a carbon fiber precursor solution having a solid content of less than 10 wt % onto the exposed surface of the columnar silicon anode, the carbon fiber precursor solution comprising carbon nanotubes, a polymer dispersant, and a solvent; and

[0035] subjecting the deposited carbon fiber precursor solution, the pillared silicon anode, and the anode current collector to elevated temperatures for a period of time effective to evaporate the solvent and form a carbon fiber network on the exposed surfaces,

[0036] wherein the carbon fiber network is random and multi-directional, and the carbon fiber network is greater than 0 to less than 3 weight percent based on the total weight of the carbon fiber network and the columnar silicon anode, and

[0037] The columnar silicon anode comprises greater than 97 wt % silicon based on the total weight of the carbon fiber network and the columnar silicon anode.

[0038] Option 12. The method according to Option 11, wherein the elevated temperature is 80°C to 90°C.

[0039] Embodiment 13. The method according to embodiment 11, wherein the solvent comprises water or N-methyl-2-pyrrolidone.

[0040] Embodiment 14. The method according to Embodiment 11, wherein the anode current collector has a surface roughness Rz of 0.1 μm to 12 μm.

[0041] Option 15. A method according to Option 11, wherein the polymer dispersant includes poly(vinylidene fluoride) (PVDF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), poly(tetrafluoroethylene) (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), nitrile rubber (NBR) or styrene ethylene butylene styrene copolymer (SEBS).

[0042] Option 16. A method according to Option 11, wherein the carbon nanotubes have a diameter of about 1 to about 6 nanometers (nm), a thickness of less than 0.1 nm, and a length of greater than 1 μm.

[0043] Option 17. A method according to Option 11, wherein the carbon fiber precursor solution further contains a carbon material, and the carbon material includes acetylene black, graphene and / or graphite.

[0044] Embodiment 18. A rechargeable lithium-ion battery pack comprising:

[0045] a cathode current collector having a thickness of about 4 to about 30 μm externally connected to a support, the cathode current collector comprising aluminum;

[0046] a cathode on the cathode current collector;

[0047] An anode current collector having a thickness of about 4 to about 30 μm externally connected to a load, wherein the anode current collector is made of one or more materials selected from the group consisting of copper, stainless steel, nickel, iron, titanium, tin (Sn) and alloys thereof, and wherein the anode current collector has a surface roughness R of 0.1 μm to 12 μm z ;

[0048] A columnar silicon anode on the anode current collector, the columnar silicon anode comprising a plurality of spherical silicon pillars and a carbon fiber network on exposed surfaces of the spherical silicon pillars, wherein the columnar silicon anode is deposited by plasma vapor deposition and has a thickness of 1 μm to about 80 μm, wherein the columnar silicon anode contains greater than 97 wt % silicon, and wherein the columnar silicon anode has a capacity of about 0.5 to about 20 mAh / cm 2 area capacity; and

[0049] A porous separator between the cathode and the columnar silicon anode.

[0050] Option 19. A lithium-ion battery according to Option 18, further comprising a liquid electrolyte in the cathode, the columnar silicon anode and the porous separator, wherein the liquid electrolyte comprises a lithium salt and an organic solvent, wherein the liquid electrolyte comprises a lithium salt, an organic solvent and optional additives, wherein the lithium salt comprises LiPF6, LiBF4, lithium bis(oxalate)borate, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiAsF6, LiC(CF3SO2)3, LiClO4, Li 1+x Al x Ti 2-x (PO4)3 and LiTFSI, and wherein the organic solvent comprises ethylene carbonate, diethyl carbonate, propylene carbonate, fluoroethylene carbonate (FEC) and combinations thereof.

[0051] Option 20. A lithium-ion battery pack according to Option 18, wherein the separator is a solid electrolyte, and the solid electrolyte is in the cathode and the columnar silicon anode, wherein the solid electrolyte is selected from pseudo-binary sulfides, pseudo-ternary sulfides, pseudo-quaternary sulfides, halide-based solid electrolytes and hydride-based solid electrolytes.

[0052] The above features and advantages and other features and advantages of the present disclosure are apparent from the following detailed description when taken in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Additional features, advantages and details are shown, by way of example only, in the following detailed description, which refers to the accompanying drawings, in which:

[0054] Figure 1 schematically illustrates a columnar silicon anode layer including a spider-web-like carbon network thereon on a copper current collector according to one or more embodiments of the present disclosure;

[0055] Figure 2 schematically illustrates a single silicon pillar according to one or more embodiments of the present disclosure;

[0056] Figure 3 is a top-down scanning electron micrograph depicting a silicon anode columnar surface including a spiderweb-like carbon fiber network thereon according to one or more embodiments of the present disclosure;

[0057] Figure 4 schematically illustrates a liquid-based electrolytic lithium-ion battery structure including a silicon anode according to one or more embodiments of the present disclosure;

[0058] Figure 5 schematically illustrates room temperature cycling of a lithium-ion battery configuration including a columnar silicon anode with and without a spiderweb-like carbon fiber network according to one or more embodiments of the present disclosure;

[0059] Figure 6 schematically illustrates rate capabilities of lithium-ion battery configurations including columnar silicon anodes with and without spiderweb-like carbon fiber networks according to one or more embodiments of the present disclosure;

[0060] Figure 7 schematically illustrates discharge curves for lithium-ion battery configurations including a columnar silicon anode with and without a spiderweb-like carbon fiber network according to one or more embodiments of the present disclosure; and

[0061] Figure 8 A solid-state electrolysis cell structure including a silicon anode according to one or more embodiments of the present disclosure is schematically illustrated. Specific implementation plan

[0062] The following description is merely exemplary in nature and is not intended to limit the present disclosure, its application, or uses.

[0063] According to an exemplary embodiment, a liquid or solid-state lithium-ion battery pack structure is disclosed, which includes a columnar silicon anode having a spider-web-like carbon fiber network thereon. The presence of a spider-web-like carbon fiber network on the columnar silicon anode, which is highly conductive, enhances the power capacity of the battery pack, especially at higher current rates. In addition, the presence of the spider-web-like carbon fiber network can be used as a protective layer for the columnar silicon anode of the lithium-ion battery pack to reduce silicon powdering that may occur due to volume expansion and contraction during the cycle process, which is used to effectively improve the battery cycle capacity and service life. Therefore, the columnar silicon anode including a spider-web-like carbon fiber network can be advantageously implemented in lithium-ion batteries for high power and high energy applications.

[0064] Conventional techniques related to lithium-ion battery manufacturing may or may not be described in detail herein. In addition, the various tasks and process steps described herein may be incorporated into a more comprehensive procedure or method having additional steps or functionality not described in detail herein. In particular, the various steps in the lithium-ion battery manufacturing method are well known, so for the sake of brevity, many conventional steps will only be briefly mentioned herein or will be omitted entirely without providing well-known process details.

[0065] For ease of description, spatially relative terms, such as "below," "below," "down," "above," "on," etc., may be used herein to describe the relationship of an element or feature shown in the drawings to one or more other elements or features. It should be understood that spatially relative terms are intended to include different orientations of the device in use or operation in addition to the orientation shown in the drawings. For example, if the device in the drawings is turned over, the elements described as being "below" or "below" other elements or features will be oriented to be "above" the other elements or features. Therefore, the term "below" can include both above and below orientations. The device can be oriented in other ways (rotated 90 degrees or in other orientations), and the spatially relative descriptions used herein are interpreted accordingly.

[0066] The following definitions and abbreviations are used to interpret the claims and specification. As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, mixture, process, method, article, or apparatus that includes a list of elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, mixture, process, method, article, or apparatus.

[0067] The terms "one" and "a kind of" do not indicate a limitation of quantity, but rather indicate the presence of at least one of the referenced items. Unless the context clearly indicates otherwise, the term "or" means "and / or". Reference to "aspects" throughout the specification means that specific elements (e.g., features, structures, steps, or characteristics) described in conjunction with the aspect are included in at least one aspect described herein, and may or may not be present in other aspects. In addition, it should be understood that the described elements may be combined in various aspects in any suitable manner. In addition, the terms "upper", "lower", "top", "bottom", "left", and "right" and their derivatives shall relate to the described structures as they are oriented in the accompanying drawings. The same numbers in the various drawings may represent the same structural components or parts thereof.

[0068] When an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element or intervening elements may also be present. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements present.

[0069] Unless specified to the contrary herein, all test standards are the most recent standards in effect on the filing date of this application, or, if priority is claimed, the filing date of the earliest priority application in which the test standards appear.

[0070] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.

[0071] Reference now Figure 1 , schematically showing a cross-sectional view of a columnar silicon anode 10 according to the present disclosure disposed on an anode current collector 12. Typically, the anode and cathode current collector of a lithium-ion battery are selected to be electrochemically stable to oxidizing and reducing environments during charging and discharging of the battery. The columnar silicon anode 10 includes a plurality of silicon pillars 14 and a spiderweb-like carbon fiber network 16 formed on the exposed surface of each silicon pillar 14 and bridging adjacent silicon pillars 14. The silicon pillars 14 are typically spherical columnar structures that provide a high interface area to facilitate charge transfer and may have a low porosity to increase energy density. The spiderweb-like carbon fiber network 16 deposited on the silicon pillars 14 has a much higher electronic conductivity than silicon semiconductors and provides a favorable electron conduction path for high-power silicon anodes.

[0072] like Figure 2 As shown, the a and b dimensions of the spherical silicon pillars 14 typically have a length of about 0.5 to about 40 micrometers (μm). For example, the a dimension may have a length dimension of 3.5 μm, and the b dimension may have a length dimension of 3.0 μm. Depending on the deposition parameters, the area capacity provided by the columnar silicon anode of the layer including the silicon pillars 14 may be 0.5 to about 20 milliampere hours per square centimeter (mAh / cm 2In one or more embodiments, the columnar silicon anode is configured to provide about 2 to about 4 mAh / cm 2 In one or more embodiments, the resulting silicon pillars 14 are greater than about 99 weight percent (wt%) silicon.

[0073] Reference to the term "spider-web" is not intended to imply a particular shape and structure of the spider-web carbon fiber network 16 on the silicon pillars 14. The spider-web carbon fiber network 16 is generally a non-repeating pattern of randomly deposited carbon fibers and is non-directional to provide strength and reinforcement in multiple directions. In one or more embodiments, the spider-web carbon fiber network 16 is greater than about 0.05 weight percent (wt%) to less than about 3 wt% based on the total weight of the silicon pillars 14 and the spider-web carbon fiber network 16.

[0074] In one or more embodiments, the anode current collector 12 is roughened to increase its surface area and improve adhesion for attaching and growing spherical silicon pillars 14 thereon. In one or more embodiments, the anode current collector 12 has a surface roughness (Rz) of about 0.1 micrometers (μm) to about 12 μm. The anode current collector 12 may have a thickness of about 4 μm to about 30 μm and may be in the form of a foil. For example, the anode current collector 12 may have a thickness of about 14 μm. The anode current collector 12 is made of one or more materials selected from copper, stainless steel, nickel, iron, titanium, tin and alloys thereof. In other embodiments, the current collector is a coated foil of graphene or a carbon-coated stainless steel foil.

[0075] The method of forming the pillared silicon anode 10 including a plurality of silicon pillars 14 and a spider web-like carbon fiber network 16 thereon generally comprises cleaning the surface of the anode current collector 12 with a suitable solvent, such as isopropyl alcohol, for example, to remove any contaminants and oxides. The surface is then rinsed with distilled water and dried.

[0076] A plurality of silicon pillars 14 may be deposited onto the clean anode current collector 12 using plasma vapor deposition (PVD). PVD generally involves depositing silicon onto a substrate (e.g., anode current collector 12) by evaporation or sputtering of a silicon target material. For example, the PVD method may be a pulsed direct current (DC) magnetron sputtering method using a silicon target (e.g., n-type; 99.995%) in an inert atmosphere. During sputtering, silicon is ejected from the silicon target material and deposited onto the anode current collector 12. As is generally known in the art, a plurality of silicon pillars 14 (i.e., columnar silicon structures) may be formed by controlling deposition parameters such as temperature, deposition rate, gas composition, and the like. The resulting columnar silicon structure may be annealed to remove any residual stress and promote further growth of the columnar structure.

[0077] Once a plurality of silicon pillars 14 are formed on the anode current collector 12, a spider web carbon fiber network 16 is then deposited thereon by mixing a dilute precursor solution containing carbon nanotubes, a polymer dispersant, and a processing solvent in which the polymer dispersant is dissolved, such as water, N-methyl-2-pyrrolidone, or a similar solvent. The total solid content (carbon nanotubes and polymer dispersant) in the precursor solution is generally low. In one or more embodiments, the total solid content is less than 10% by weight. In one or more other embodiments, the total solid content is less than 3% by weight, and in yet one or more embodiments, the total solid content is less than 1% by weight. The precursor solution can be sprayed onto a plurality of silicon pillars 14 and then exposed to mild solvent evaporation at an elevated temperature of about 80° C. to 90° C., for example, for a period of time that is effective to completely remove the solvent. Once the solvent is removed, a spider web carbon fiber network 16 is formed. As described above, in one or more embodiments, the spider web carbon network 16 is greater than 0.05 to less than 3 weight percent based on the total weight of the plurality of silicon pillars 14 and the spider web carbon fiber network 16. The amount of silicon in the pillared silicon anode 10 is greater than 97 weight percent based on the total weight of the plurality of silicon pillars 14 and the spiderweb-like carbon fiber network 16. For example, the amount of carbon deposited during the formation of the spiderweb-like carbon fiber network can be readily determined using thermogravimetric analysis, which is an analytical technique that involves monitoring weight changes upon application of heat and / or pyrolysis.

[0078] In one or more embodiments, the spider web carbon fiber network 16 is formed by carbon nanotubes (CNTs), which may include single-walled carbon nanotubes (SWCNTs), double-walled carbon nanotubes (DWCNTs), multi-walled carbon nanotubes (MWCNTs) or a combination thereof. Carbon nanotubes are generally cylindrical carbon structures with diameters in the nanometer (nm) level (typically a few nanometers) and lengths that may range from micrometers to millimeters. SWCNTs specifically refer to nanotubes composed of single-layer graphene rolled into seamless cylinders, while DWCNTs include two layers of concentric cylinders, and multi-walled CNTs refer to more than two concentric cylindrical layers. Suitable SWCNTs, DWCNTs, and multi-walled carbon nanotubes for forming spider web carbon fiber networks typically have a length greater than about 1 micrometer (μm), a diameter of about 1 nm to about 6 nm, and a thickness less than 0.1 nanometer (nm), although larger or smaller diameters and thicknesses may be used. Alternatively, vapor-grown carbon fibers having the above-mentioned sizes may be used. In one or more embodiments, the blend of carbon nanotubes can be mixed with other types of carbon additive materials in the precursor solution during the formation of the spiderweb carbon fiber network (e.g., Super P available from TIMCAL). TM , Ketjenblack (a type of acetylene black) commercially available from Cabot Corporation, acetylene black, graphite conductive agents such as KS-6, KS-15, SO, SEG-6, etc., and graphene).

[0079] Exemplary polymer dispersants include, but are not limited to, poly(vinylidene fluoride) (PVDF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), poly(tetrafluoroethylene) (PTFE), sodium carboxymethylcellulose (CMC), styrene-butadiene rubber (SBR), nitrile rubber (NBR), styrene ethylene butylene styrene copolymer (SEBS), etc. The polymer dispersant helps the dispersibility of the carbon nanotubes in the precursor solution (i.e., prevents aggregation).

[0080] Figure 3 is a scanning electron micrograph depicting the top surface of an exemplary pillar-shaped silicon anode 14 including a spider-web-like carbon fiber network 16 thereon. As shown, the spider-web-like carbon fiber network is randomly formed directly on the exposed surface of each silicon pillar and also bridges the surfaces of adjacent silicon pillars. The spider-web-like carbon fiber network is random and multi-directional.

[0081] Figure 4 An exemplary liquid-based lithium-ion battery cell 50 is illustrated. The lithium-ion battery cell 50, also referred to as an electrochemical cell, includes a single cell, but may also include more than one cell. The lithium-ion battery cell 50 typically includes an anode current collector 52, which is typically a copper current collector, and a cathode current collector 54, which is typically an aluminum current collector. The anode and cathode current collectors 52, 54, respectively, may be appropriately externally connected to a load or recharging power source (not shown). A columnar silicon anode 56 including a spider web-like carbon fiber network thereon covers the anode current collector 52, and a lithium-containing metal oxide-based cathode 58 covers the cathode current collector 54. A porous plastic spacer or separator 60 is disposed between the columnar silicon anode 56 including a spider web-like carbon fiber network thereon and the cathode 58. A liquid electrolyte 62 is dispersed within the porous plastic spacer or separator 60, the silicon anode layer 56, and the lithium-containing metal oxide-based composite cathode layer 58.

[0082] The lithium-containing metal oxide-based cathode 58 typically comprises 30 to 98 weight percent active cathode material, 0 to 30 weight percent conductive additive, and 0 to 20 weight percent binder, wherein the weight percents are based on the total weight of the lithium-containing metal oxide-based cathode 58. The lithium-containing metal oxide-based cathode can have a thickness of about 10 μm to about 500 μm, for example 40 μm.

[0083] Exemplary active cathode materials include, but are not limited to, lithium-containing metal oxide-based composites, such as lithium cobalt oxide (LCO), lithium nickel manganese cobalt oxide (NMC), lithium iron phosphate (LFP), lithium manganese oxide-lithium manganese iron phosphate (LMO-LMFP), lithium manganese oxide (LMO), lithium nickel cobalt aluminum oxide (NCA), lithium titanate (LTO), and the like.

[0084] The conductive additive includes one or more materials selected from carbon black, graphite, graphene, graphene oxide, Super P (SP), acetylene black, carbon nanofibers, carbon nanotubes, and other electronic conductive additives.

[0085] Examples of binders include one or more materials selected from polytetrafluoroethylene (PTFE), sodium carboxymethylcellulose (CMC), styrene-butadiene rubber (SBR), poly(vinylidene fluoride) (PVDF), nitrile rubber (NBR), styrene ethylene butylene styrene copolymer (SEBS), styrene butadiene styrene copolymer (SBS), and other suitable binders.

[0086] An exemplary separator 60 according to one or more embodiments may include polyethylene (PE), polypropylene (PP), polyacetylene, combinations thereof, etc. The separator generally has a porosity of about 40 to about 60% and a thickness of about 8 to about 20 μm.

[0087] The liquid electrolyte 62 is a liquid medium that enables lithium ions to move between the lithium-containing metal oxide-based cathode 58 and the columnar silicon anode 56 on which the spider-like carbon fiber network is included. The liquid electrolyte 62 generally comprises a lithium salt, an organic solvent, and an additive. Examples of suitable salts include LiPF6, LiBF4, lithium bis(oxalate)borate, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiAsF6, LiC(CF3SO2)3, LiClO4, Li 1+x Al x Ti 2-x (PO4)3 and LiTFSI. Examples of organic solvents are ethylene carbonate, diethyl carbonate, propylene carbonate, fluoroethylene carbonate (FEC) and combinations thereof.

[0088] When the liquid-based lithium-ion battery cell 50 is fully charged, lithium ions have been transported from the lithium-containing metal oxide-based cathode layer 58 via the liquid electrolyte 62 to the columnar silicon anode 56 (including a spider web-like carbon fiber network thereon) to produce a lithium silicon compound such as Li 21 Si5, which has a maximum capacity significantly higher than that of the graphite anode.

[0089] use Figure 6-8The results are shown in Figure 2, and the electrochemical properties of liquid-based lithium-ion battery cells including columnar silicon anodes with and without spider-web carbon fiber networks were evaluated. In the following experiments, the lithium-ion battery cells included a copper current collector with a thickness of 20 μm, the same columnar silicon anode with and without spider-web carbon fiber networks, a separator with a thickness of 20 μm and a porosity of 45% formed of polyacetylene and polypropylene; a cathode formed of LMFP / LMO / SP / PVDF=46 / 46 / 4 / 4 (wt%), and its loading was about 1.1 mAh / cm 2 , and an aluminum cathode current collector with a thickness of 20 μm.

[0090] exist Figure 5 In the present invention, the cycling performance of a lithium-ion battery pack configuration including a silicon anode without a spider-web carbon network (Si-w / oC) and a configuration including a silicon anode with a spider-web carbon network (Si-w / C) at room temperature was evaluated. After about 60 cycles, the lithium-ion battery pack including the Si-w / oC anode began to show a loss in capacity retention percentage compared to the same lithium-ion battery pack configuration including the Si-w / C anode, and the loss was exacerbated after 100 cycles. The capacity retention percentage of Si-w / oC deteriorated significantly to a capacity retention rate of about 70% after 100 cycles, and it is believed that this is attributed to electrical contact loss caused by volume expansion. In contrast, the capacity retention percentage of the lithium-ion battery pack including the Si-w / C anode is essentially linear, about 88% after 100 cycles, which advantageously demonstrates the improved electronic conduction and freedom from volume expansion during charging due to the presence of the spider-web carbon fiber network.

[0091] Figure 6The rate performance of a lithium-ion battery pack configuration including a silicon anode (Si-w / oC) without a spider-web carbon network and a configuration including a silicon anode (Si-w / C) with a spider-web carbon network is schematically illustrated. The discharge rate performance in a lithium-ion battery pack generally refers to the extent to which the battery pack can deliver charge at different rates or current levels, which is generally referred to as the C-current rate (i.e., it is a measure of how fast the battery pack can be discharged while maintaining its capacity and performance). The C-rate represents the current at which the battery pack discharges for its rated capacity. For example, a battery pack discharged at a 1C-rate will take one hour to fully discharge, while a 2C-rate will discharge the battery pack within half an hour. Higher C-rates, such as 5C or 10C, represent much faster discharge rates. As shown in the figure, the capacity retention percentages of 3 cycles were measured at the different rates shown. At higher C-rates, the capacity retention percentage of the lithium-ion battery pack including the Si-w / oC anode is significantly lower than that of the lithium-ion battery pack including the Si-w / C anode, with the difference being higher as the C-rate increases. Clearly, the spider-web-like carbon fiber network on the columnar silicon anode enhances the battery pack discharge power capability, especially at the illustrated 15C-rate and 20C-rate.

[0092] exist Figure 7 In the figure, the discharge curves of a lithium-ion battery pack configuration including a silicon anode without a spider web carbon network (Si-w / oC) and a configuration including a silicon anode with a spider web carbon network (Si-w / C) at a 15C-rate are illustrated. The discharge curve of a lithium-ion battery pack refers to the relationship between the battery pack voltage and its remaining capacity during the discharge cycle. It illustrates how the voltage of the battery pack decreases as the capacity is exhausted. As shown, in the lithium-ion battery pack including the Si-w / C anode, the capacity retention rate is much higher.

[0093] Figure 8 A solid-state lithium-ion battery cell 100 is illustrated according to one or more other embodiments. The solid-state lithium-ion battery 100 includes an anode current collector 102 and a cathode current collector 104. A columnar silicon anode 106 including a spider web-like carbon fiber network as previously described is disposed on the anode current collector 102, and a cathode 108 is disposed on the cathode current collector 104. A separator 110 formed of a solid electrolyte 112 is between the columnar silicon anode 106 including a spider web-like carbon fiber network and the cathode 108, which may also include a solid electrolyte 112.

[0094] The cathode 108 in the solid-state battery 100 may include a solid electrolyte (in the range of 1 to 50 wt%), 30 to 98 wt% of a cathode active material, 0 to 30 wt% of a conductive additive, and 0 to 20 wt% of a binder. In some examples, the cathode 108 has a thickness of 10 μm to 500 μm (e.g., 40 μm).

[0095] In some examples, the cathode active material includes one or more materials selected from rock salt layered oxides, spinels, multi-anion cathodes, lithium transition metal oxides, surface coated and / or doped cathode materials, and low voltage cathode materials.

[0096] Examples of rock salt layered oxides include LiCoO2, LiNi x Mn y Co 1-x-y O2、LiNi x Mn y Al 1-x-y O2、LiNi x Mn 1-x O2、Li 1+x MO2. Examples of spinels include LiMn2O4, LiNi 0.5 Mn 1.5 O4. Examples of polyanion cathodes include LiV2(PO4)3. Examples of surface-coated and / or doped cathode materials include LiNbO3-coated LiMn2O4, Li2ZrO3 or Li3PO4-coated LiNi x Mn y Co 1-x-y O2 and Al-doped LiMn2O4. Examples of low voltage cathode materials include lithiated metal oxides / sulfides (eg, LiTiS2), lithium sulfide, and sulfur.

[0097] In some examples, the conductive additive includes one or more materials selected from carbon black, graphite, graphene, graphene oxide, Super P, acetylene black, carbon nanofibers, carbon nanotubes, and other electronic conductive additives. Examples of binders include one or more materials selected from polytetrafluoroethylene (PTFE), sodium carboxymethylcellulose (CMC), styrene-butadiene rubber (SBR), poly(vinylidene fluoride) (PVDF), nitrile rubber (NBR), styrene ethylene butylene styrene copolymer (SEBS), styrene butadiene styrene copolymer (SBS), and other suitable binders.

[0098] In some examples, the solid electrolyte in the separator layer and / or the cathode electrode is selected from pseudo binary sulfides, pseudo ternary sulfides, pseudo quaternary sulfides, halide-based solid electrolytes, and hydride-based solid electrolytes.

[0099] Examples of pseudo binary sulfides include the Li2S-P2S5 system (Li3PS4, Li7P3S 11 and Li 9.6 P3S 12), Li2S-SnS2 system (Li4SnS4), Li2S-SiS2 system, Li2S-GeS2 system, Li2S-B2S3 system, Li2S-Ga2S3 system, Li2S-P2S3 system, Li2S-Al2S3 system. Examples of pseudo-ternary sulfides include Li2O-Li2S-P2S5 system, Li2S-P2S5-P2O5 system, Li2S-P2S5-GeS2 system (Li 3.25 Ge 0.25 P 0.75 S4 and Li 10 GeP2S 12 ), Li2S-P2S5-LiX (X = F, Cl, Br, I) system (Li6PS5Br, Li6PS5Cl, Li7P2S8I and Li4PS4I), Li2S-As2S5-SnS2 system (Li 3.833 Sn 0.833 As 0.166 S4), Li2S-P2S5-Al2S3 system, Li2S-LiX-SiS2 (X=F, Cl, Br, I) system and 0.4LiI·0.6Li4SnS4 and Li 11 Si2PS 12 Examples of pseudo-quaternary sulfides include the Li2O-Li2S-P2S5-P2O5 system, Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 、Li7P 2.9 Mn 0.1 S 10.7 I 0.3 and Li 10 .35[Sn 0.27 Si 1.08 ]P 1.65 S 12 .

[0100] Examples of halide-based solid electrolytes include Li3YCl6, Li3InCl6, Li3YBr6, LiI, Li2CdCl4, Li2MgCl4, Li2CdI4, Li2ZnI4, Li3OCl. Examples of hydride-based solid electrolytes include LiBH4, LiBH4-LiX (X = Cl, Br or I), LiNH2, Li2NH, LiBH4-LiNH2, Li3AlH6. In other examples, other types of solid electrolytes with low grain boundary resistance can be used.

[0101] Although the above disclosure has been described with reference to exemplary embodiments, it will be appreciated by those skilled in the art that various changes may be made and elements thereof may be replaced with equivalents without departing from the scope of the present disclosure. In addition, many modifications may be made to adapt specific circumstances or materials to the teachings of the present disclosure without departing from the substantive scope of the present disclosure. Therefore, the present disclosure is not limited to the specific embodiments disclosed, but will include all embodiments falling within its scope.

Claims

1. A columnar silicon anode for a lithium-ion battery pack, comprising: a plurality of spherical silicon pillars; as well as A carbon fiber network on the exposed surface of the spherical silicon pillar, wherein the silicon in the plurality of spherical silicon pillars is greater than 97 weight percent, and wherein the carbon fiber network is about 0.05 weight percent to less than 3 weight percent, wherein the weight percentages are based on the total weight of the plurality of spherical silicon pillars and the carbon fiber network.

2. The columnar silicon anode of claim 1, wherein the carbon fiber network is random and multi-directional.

3. The columnar silicon anode of claim 1, wherein the carbon fiber network further comprises greater than 0 to 3 wt% of a polymer additive.

4. The columnar silicon anode of claim 1, wherein the carbon fiber network comprises carbon nanotubes, wherein the carbon nanotubes have a length greater than about 1 micrometer (μm), a diameter of about 1 nm to about 6 nm, and a thickness less than 0.1 nanometers (nm). 5 . The columnar silicon anode according to claim 4 , wherein the carbon nanotubes include single-walled carbon nanotubes, double-walled carbon nanotubes and / or multi-walled nanotubes.

6. The columnar silicon anode of claim 4, wherein the carbon fiber network further comprises one or more carbon additive materials.

7. The pillared silicon anode of claim 1, wherein the plurality of spherical silicon pillars are deposited onto the anode current collector by DC magnetron sputtering.

8. The pillar-shaped silicon anode of claim 1, wherein the silicon anode has an areal capacity of about 0.5 to about 20 milliampere hours per square centimeter.

9. A method for forming a carbon fiber network on a columnar silicon anode of a lithium ion battery, the method comprising: providing a columnar silicon anode on an anode current collector, wherein the columnar silicon anode comprises a plurality of spherical silicon pillars deposited onto the anode current collector by plasma vapor deposition; depositing a carbon fiber precursor solution having a solid content of less than 10 wt % onto the exposed surface of the columnar silicon anode, the carbon fiber precursor solution comprising carbon nanotubes, a polymer dispersant, and a solvent; as well as subjecting the deposited carbon fiber precursor solution, the pillared silicon anode, and the anode current collector to elevated temperatures for a period of time effective to evaporate the solvent and form a carbon fiber network on the exposed surfaces, wherein the carbon fiber network is random and multi-directional, and the carbon fiber network is greater than 0 to less than 3 weight percent based on the total weight of the carbon fiber network and the columnar silicon anode, and The columnar silicon anode comprises greater than 97 wt % silicon based on the total weight of the carbon fiber network and the columnar silicon anode.

10. The method of claim 9, wherein the carbon nanotubes have a diameter of about 1 to about 6 nanometers (nm), a thickness of less than 0.1 nm, and a length of greater than 1 μm.